Thermal comfort of various building layouts with a proposed discomfort index range for tropical climate - Mohd. Fadhil, Md. Din (Elsevier Ltd., 2014)
Recent years have seen issues related to thermal comfort gaining more momentum in tropical countries. The thermal adaptation and thermal comfort index play a significant role in evaluating the outdoor thermal comfort. In this study, the aim is to capture the thermal sensation of respondents at outdoor environment through questionnaire survey and to determine the discomfort index (DI) to measure the thermal discomfort level. The results indicated that most respondents had thermally accepted the existing environment conditions although they felt slightly warm and hot. A strong correlation between thermal sensation and measured DI was also identified. As a result, a new discomfort index range had been proposed in association with local climate and thermal sensation of occupants to evaluate thermal comfort. The results had proved that the respondents can adapt to a wider range of thermal conditions. Validation of the questionnaire data at Putrajaya was done to prove that the thermal sensation in both Putrajaya and UTM was almost similar since they are located in the same tropical climate region. Hence, a quantitative field study on building layouts was done to facilitate the outdoor human discomfort level based on newly proposed discomfort index range. The results showed that slightly shaded building layouts of type- A and B exhibited higher temperature and discomfort index. The resultant adaptive thermal comfort theory was incorporated into the field studies as well. Finally, the study also showed that the DI values were highly dependent on ambient temperature and relative humidity but had fewer effects for solar radiation intensity.